Differences in clinical characteristics of head injuries to snowboarders by skill level. The American journal of sports medicine - Koyama, S.; Fukuda, O.; Hayashi, N.; Endo, S. (The American Journal of Sports Medicine, 2011)
Background: Many reports have compared head injuries between snowboarding and skiing. However, detailed studies comparing snowboarding head injuries between beginners and intermediates/experts have been lacking.